Severe Bilateral Hyperkeratosis of the Nipples and Areolae: A Case Report and Literature Review - Wei, Jiaying; Li, Qingshu; Wu, He; Yin, Xuedong; Ren, Guosheng (Frontiers in Medicine, 2022)
Background Hyperkeratosis of the nipple and areola (HNA) is a rare skin disease with unknown etiology. Some patients are misdiagnosed or never diagnosed, especially during the early stage of this disease. In addition, the mechanism involved in the development of HNA is still unknown, and genomic alterations have not been reported anywhere. Case Information A 26-year-old female suffered gradual bilateral areola thickening and enlargement, with accompanying intense itching, and was diagnosed with HNA at the First Affiliated Hospital of Chongqing Medical University. No obvious abnormalities were found in laboratory test examinations such as hormone testing for estrogen, progesterone, or prolactin. Typical papillomatous skin with orthokeratotic hyperkeratosis and numerous infiltrating lymphocytes was detected through a histopathological examination. The results from RNA-sequencing showed that the molecular expression between HNA and a normal nipple and areola (NNA) was obviously different. No significant difference was found in the bilateral lesions. In addition, immune-related cell signaling pathways were overactivated in HNA compared to the control HNA. Conclusion The typical symptoms, clinical features, and histopathological alterations presented in this case lead to a profound understanding of HNA, which can avoid the misdiagnosis and missed diagnosis of this disease at an early stage. The dysfunction of the local immune system, which was demonstrated by pathological examination and genomic analysis, suggests that anti-autoimmune therapy, such as steroid medication, may be an effective treatment for HNA at an early stage.